Gene expression of selected apoptotic markers in Human Oral Carcinoma (HSC-3) cell lines trewated with myrmecodia pendans plant extract - Iskandar, Siti Hajar; Wan Yusry, Wan Nur Aisyah; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari (2019)
Introduction: Myrmecodia pendans (M. pendans), also known as Sarang Semut is an epiphyte with potential as a new therapeutic agent. Recently, we reported that M. pendans induced apoptotic activity in human oral squamous carcinoma (HSC-3) cell line. This study aimed to study how M. pendans extract affected apoptotic markers BAX/BCL-2 expression. Materials and methods: M. pendans was purchased from West Papua, Indonesia. The hypocotyl was allowed to dry thoroughly, then extracted aqueously. The extract was kept at -80 °C before freeze drying. The crude extract was used in the experiments. HSC-3 cells were cultured in Dulbecco’s Modified Essential Medium, then exposed to M. pendans at 2.5, 5.0 and 7.5 mg/ml for 24 and 48 h. Doxorubicin (0.005 mg/ml) was used as positive control. BAX and BCL-2 expression was analysed by Quantitative Real Time Polymerase Chain Reaction. Results: BAX and BCL-2 expression in HSC-3 cells was affected by M. pendans. At 24 h, highest levels of BAX and BCL-2 were observed with M. pendans at 2.5 mg/ml, while downregulation was observed at 5 mg/ml. However, after 48 h, BAX and BCL-2 were downregulated at all concentrations. The ratio of BAX/ BCL-2 in HSC-3 cells at 24 h showed significant upregulation at all treatment concentrations, but was downregulated after 48 h. Conclusion: M. pendans extract induced apoptotic activity in HSC-3 cells. This study suggests that induction of apoptosis in HSC-3 cell line is regulated via the pro-apoptotic (BAX) and anti- apoptotic (BCL -2) pathways.